Nonbanks, banks, and monetary policy: U.S. loan-level evidence since the 1990s - David Elliott; Ralf R. Meisenzahl; José-Luis Peydró; Bryce C. Turner (Federal Reserve Bank of Chicago, 2022)
We show that nonbanks (funds, shadow banks, fintech) affect the transmission of monetary policy to output, prices and the distribution of risk via credit supply. For identification, we exploit exhaustive US loan-level data since the 1990s, borrowerlender relationships and Gertler-Karadi monetary policy shocks. Higher policy rates shift credit supply from banks to nonbanks, thereby largely neutralizing associated consumption effects (via consumer loans), while just attenuating firm investment and house price spillovers (via corporate loans and mortgages). Moreover, different from the risk-taking channel, higher policy rates increase risk-taking, as less-regulated, fragile nonbanks -in all credit markets- expand supply to riskier borrowers.
Keywords: E51; E52; G21; G23; G28; 330; Nonbank Intermediaries; Banks; Monetary Policy Transmission; Household and Corporate Loans; Credit and Risk-Taking Channel